The origin of collected charge and open-circuit voltage in blended polyfluorene photovoltaic devices - Snaith, H; Greenham, N; Friend, R (2004)
The transport properties of the blended polyfluorene layers were studied using layered structures containing both pristine and the blended layers. It was shown that for a polymer blend device where there is a fine scale of phase separation, only charges generated close to either electrode can be collected. The open-circuit voltage of a polymer blend device was found to be lower than that of a bi-layer device as a result of direct paths from cathode to anode of each component of the blend. The results show that a charge injection barrier from the electrodes into the polymer film helps to retain a high open-circuit voltage in the blend.